ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA MATERI PERBANDINGAN DI SMPN 58 JAKARTA KELAS VII.2 - Ruth Yuni Kartika; Jitu Halomoan Lumbantoruan; Candra Ditasona (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
The daily test results for student of class VII.2 SMPN 58 Jakarta on the Comparison material showed that 30 out of 36 students got scores below the MCML (Minimum Criteria of Mastery Learning). The low test results were not always caused by the level of students’ intellegence, but it could occur because students have difficulty learning, as a student with difficulty learning do not necessarily have inadequate intellegence. The research aimed to determine the type or form of learning difficulties and the causes for students during their learning. The research used qualitative method with a descriptive qualitative approach. The population in this research were 30 students of class VII.2 SMPN 58 Jakarta who got daily test scores below the MCML for Comparison material. The interview subjects were 6 out 30 students who were selected through purposive proportional random sampling, and a Math teacher in this class. The results obtained based on the test analysis and interviews found student difficulties, such as in interpreting language, in unsderstanding and using concepts, in using data, and in technical difficulty (counting). Then, the results obtained based on the anlysis questionnaire analysis and interviews found that students had difficulties due to their lack of confidence and mortification in learning, and teacher who didn’t understand each student personally.